Maternal mowing effect on seed traits of an invasive weed, Erigeron annuus in Farmland - Xiao, Hui Yong; Jiang, Hua Liu; Zhen, Li; Shu, Feng Du; Zhuo, Wen Zhang; Xue, Feng Meng; Xiao, Jing Wu; Yong, Jian Wang (Universiti Kebangsaan Malaysia, 2015)
The effect of maternal mowing on seed traits of an invasive weed, Erigeron annuus, in farmland was discussed by comparing mowing plants with intact (no-mowing) plants. The maternal mowing effect resulted in the decrease of seed mass, achene size, pappus length and germination percentage and the increase of variation in achene size, pappus length, dispersal distance and germination non-uniformity. To some extent, the individuals suffered mowing might accelerate the environmental adaptation through the increase of these variations. Our study indicated the mean of mowing in farmland will restrain the growth and reproduction of weed E. annuus. However, it also increases the diversity of seeds through a more unequal provision to seeds that shares the risk and increases fitness to a wider range of heterogeneity of farmland condition.